Ibuprofen alters epoxide hydrolase activity and epoxy-oxylipin metabolites associated with different metabolic pathways in murine livers - Tiwari, Shuchita (Sci Rep, 2021)
Over the last decade oxylipins have become more recognized for their involvement in several diseases. Non-steroidal anti-inflammatory drugs (NSAIDs) such as ibuprofen are known to inhibit cyclooxygenase (COX) enzymes, but how NSAIDs affect oxylipins, in addition to COX products, in animal tissues is not well understood. Oxylipins in livers from male and female mice treated with 100 mg/kg/day of ibuprofen for 7 days were investigated. The results showed that ibuprofen treated male livers contained 7 times more altered oxylipins than ibuprofen treated female livers. In male and female livers some prostaglandins were altered, while diols, hydroxy fatty acids and epoxides were significantly altered in male livers. Some soluble epoxide hydrolase (sEH) products, such as 9,10-DiHODE were found to be decreased, while sEH substrates (such as 9(10)-EpODE and 5(6)-EpETrE) were found to be increased in male livers treated with ibuprofen, but not in ibuprofen treated female livers. The enzymatic activities of sEH and microsomal epoxide hydrolase (mEH) were elevated by ibuprofen in both males and females. Analyzing the influence of sex on the effect of ibuprofen on oxylipins and COX products showed that approximately 27% of oxylipins detected were influenced by sex. The results reveal that ibuprofen disturbs not only the COX pathway, but also the CYP450 and lipoxygenase pathways in male mice, suggesting that ibuprofen is likely to generate sex related differences in biologically active oxylipins. Increased sEH activity after ibuprofen treatment is likely to be one of the mechanisms by which the liver reduces the higher levels of EpODEs and EpETrEs.